Application of the Inquiry-Based Learning Model with Education for Sustainable Development to Enhance Critical Thinking Skills and Sustainable Awareness - Lidya Betty Setiyaningsih; Riandi Riandi; Amprasto Amprasto; Mardiyah Mardiyah (Jurnal Penelitian Pendidikan IPA, 2024)
To improve the quality of education and develop students' 21st-century competencies, particularly critical thinking, the inquiry-based learning model presents itself as a viable option to enhance students' cognitive abilities and awareness of sustainability. Incorporating Education for sustainable development into the inquiry-based learning model introduces a relevant approach to addressing contemporary global challenges, especially in sustainable development education. This research seeks to assess the enhancement of students' critical thinking skills and sustainable awareness through the application of the inquiry-based learning model infused with ESD content. The research method used in this study is a quasi-experiment with a non-equivalent control group design. This research was conducted on class X students at one of the MAN in Bandar Lampung, with each class consisting of 35 and 36 students. Data were obtained from the results of pre-tests and post-tests of critical thinking skills, sustainable awareness questionnaires, and student response surveys. The results of the study indicate that there was an improvement in students' critical thinking skills between the experimental and control classes. There was also a significant difference in sustainable awareness between the experimental and control classes. The inquiry-based learning model integrated with ESD content showed a significant and fairly strong positive correlation between students' critical thinking skills and sustainable awareness